β‑catenin Immunohistochemical expression in papillary thyroid cancer versus benign thyroid lesions in a sample of Iraqi patients (Texas Journal of Medical Science, 2022)
Papillary thyroid cancer is the commonest one among thyroid cancers. β - catenin is thought to be involved in thyroid cell to cell adhesion and proliferation. This study was aimed to determine β -catenin expression in benign and malignant tumors and its correlation to tumor differentiation. Methods: Fifty three paraffin blocks of malignant and benign thyroid samples were collected from patients underwent thyroidectomy. Paraffin blocks were stained with Rabbit monoclonal to β -catenin. Results: Most of papillary thyroid carcinomas subtypes are well differentiated (71%). Out of 15 cases of benign thyroid tumors, 11 cases showed a membranous staining (73.3%). Out of 38 cases of papillary thyroid carcinomas, 17 cases showed a membranous staining (44.7%). There was a significantly higher cytoplasmic staining in papillary thyroid carcinomas than benign lesions (39.5% vs 20%). There was no significant nuclear staining in benign lesions and papillary thyroid carcinomas. The membranous staining was significantly lost in cases of poorly differentiated and undifferentiated papillary thyroid carcinomas. Conclusion: β‑catenin shifting from the membrane to the cytoplasm in papillary thyroid carcinoma is helpful in its differentiation from benign lesions.